KUALITAS AUDIT SEBAGAI MEKANISME TATA KELOLA ESKTERNAL PADA PERUSAHAAN INDUSTRI KEUANGAN INDONESIA - Ilona, Desi (Gapenas Publisher, 2024)
This study investigates the effect of audit quality, as proxied by Big 4 audit firm affiliation, on the financial performance of finance companies. Using a sample of 27 finance firms listed on the stock exchange over the period 2004 to 2017, the study examines differences in performance indicators between companies audited by Big 4 and non-Big 4 firms. Four key financial indicators are analyzed: Return on Assets (ROA), Return on Sales (ROS), Tobin’s Q (TQ), and Stock Return (SR). Descriptive statistics, independent samples t-tests, and effect size analyses (Cohen’s d, Hedges’ correction, and Glass’s delta) are employed to assess both statistical and practical significance of differences. The results show that companies audited by Big 4 firms have significantly higher Return on Sales, suggesting a link between audit quality and operational profitability. While ROA and TQ show favorable averages for Big 4-audited firms, the differences are not statistically significant. For stock return, only Glass’s delta indicates a significant effect, favoring non-Big 4 firms. These findings imply that Big 4 audit firms contribute to improved internal financial performance, particularly in sales profitability, although they do not consistently impact market-based outcomes. This study contributes to the literature on audit quality and corporate performance, especially in the context of the finance industry. However, the findings are subject to limitations, including the relatively small sample size and industry-specific scope. Future research is encouraged to expand the sample, update the time period, and incorporate broader measures of audit quality.